PHARMACEUTICAL EVALUATION AND TOXICOLOGICAL QUANTIFICATION OF HEAVY METALS AND ADULTERATED ALLOPATHIC CONTENTS IN RAWAND FINISHED DOSAGE FORM OF ANTIHYPERTENSIVE HERBAL PRODUCTS - Khan, Muhammad Asif; Badshah, Amir; Shahid, Muhammad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Herbal products of questionable quality create major concern for human population since their production is often notcontrolled and regulated.Material and Methods: Antihypertensive herbal products were subjected to pharmaceutical quality control parameters specified inPharmacopoeias, toxic quantification of heavy metals by flame atomic absorption spectrophotometer and adulterated allopathiccontents were quantified using advanced HPLC techniques.Results: A lot of variations in pharmaceutical parameters like moisture contents and LOD% values were observed. Also deviationsto a greater extent in weight variation, (P1, P2, P6, P12, P16, P17, P19, and P20), and hardness of the tablets of products (P1, P3, P8and P11) were found. Friability of tablets of the Products (P3, P9 and P11) was found failed. Heavy metals i-e Fe (1597.20ppm,1648ppm) in P5, P9, Pb (61.32ppm, 16.59 ppm) in P5, Cr (96.91ppm ,108.48 ppm) in P4, P14, Cd (39.53ppm, 32.31 ppm) in P11,P12, Cu (28.22ppm, 21.04 ppm) in P15, P17, Zn (80.31ppm,76.27 ppm) in P15, P16, Ni (45.46ppm,22.18ppm) in P9, P13 in toxicconcentrations were detected. Adulterated allopathic contents of Amlpdopine in higher quantities, administered according tomanufacturer dose were found in P12 (20.30 mg/day), Verapamil in P2 (93.50 mg/day), Nifedipine (38.65 mg/day) in P6. ProductsP4, P5 and P7 were found to have a combination of Amlodipine and Hydrochlorothiazide and higher concentrations were found inP5 (10.72 mg/day, 24.75 mg/day).Conclusion:. The antihypertensive herbal products contained different kind of adulterants. Our findings suggest that effectiveregulatory measures should be put in place to address this problem. This will help to decrease the toxic effects of these remedies andincrease the commercialization, internationalization and harmonization of antihypertensive herbal products.